1990
DOI: 10.1002/jsfa.2740530403
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation effects on the development and yield of determinate and indeterminate forms of autumn‐sown faba bean

Abstract: Large and erratic seasonal variations in yield of faba beans (Vicia faba L ) are attributed to the responsiveness of indeterminate cultiuars to changes in water supply. A field trial at the University of Nottingham School of Agriculture Farm examined the response of an indeterminate cultivar (Bourdon) and a determinate selection (858) to di&erent levels of water supply at diferent stages of growth. The trial was sown in the autumn of each of three consecutive seasons beginning in 1985.By limiting the availabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
2
1
Order By: Relevance
“…However, there was little increase in HI with rising seed yield. There was no correlation between TDM and HI (Table 2) These results disagree somewhat with the findings of Grashoff (1990), Pilbeam et al (1990), Silim and Saxena (1993), and De Costa et al (1997b), who reported that low HI is associated with high seed yield; therefore, high biomass may be a prerequisite to achieve high seed yields of faba bean. Sau and Mínguez (2000) reported that greater TDM production was not associated with higher seed yield due to low mobilization (reflected by a decrease in HI).…”
Section: Resultscontrasting
confidence: 62%
“…However, there was little increase in HI with rising seed yield. There was no correlation between TDM and HI (Table 2) These results disagree somewhat with the findings of Grashoff (1990), Pilbeam et al (1990), Silim and Saxena (1993), and De Costa et al (1997b), who reported that low HI is associated with high seed yield; therefore, high biomass may be a prerequisite to achieve high seed yields of faba bean. Sau and Mínguez (2000) reported that greater TDM production was not associated with higher seed yield due to low mobilization (reflected by a decrease in HI).…”
Section: Resultscontrasting
confidence: 62%
“…Even in the presence of adequate pollination, reduced light during overcast weather reduces flower retention. Faba beans are also very sensitive to water deficits during flowering and pod set (Pilbeam, Hebblethwaite, & Yusuf, 1990; Xia, 1994); these cause abscission of flowers and pods (Peat, 1983) and reduce the duration of flowering (Xia, 1994). This all supports the idea that the availability of assimilate during pod set is critical for yield determination, and that yield resilience will be enhanced if the number of flowering nodes (hence the duration of flowering) is increased.…”
Section: Discussionmentioning
confidence: 99%
“…First, it must be important to target water capture because Y bp was water limited at many sites, and many aspects of yield formation are susceptible to water deficits (Pilbeam, Duc, & Hebblethwaite, 1990; Pilbeam, Hebblethwaite, & Yusuf, 1990). Assumptions for achievement of Y bp are that water capture down to 1 m is possible whereas Bailey (1990) and Hebblethwaite (1982) consider that beans in the UK achieve 70 and 90 cm depth for spring and winter field beans (for sparse rooting, capable of extracting easily available water only).…”
Section: Discussionmentioning
confidence: 99%